ANALISIS PENALARAN PROPORSIONAL PADA SISWA KESULITAN BELAJAR MATEMATIKA DI SEKOLAH INKLUSIF - YUWONO, IMAM; PUTRI, ADELIA ANANDA (E-Jurnal Matematika, 2020)
Many Mathematical concepts require students to use proportional reasoning. Proportional reasoning can be an indication of the level of students' mastery of mathematics on subjects involving comparison problems. Problems solving with proportional reasoning can be even more challenging for students with mathematic learning disabilities. The purpose of this study was to analyze the reasoning of students of difficulty learning mathematics in inclusive schools. Research approach with qualitative methods. The results showed that the three subjects in solving four different types of problems tended to be the same. Proportional reasoning ability of the three subjects is at level 0 to 1 proportional reasoning ability.